2018
DOI: 10.3390/ijerph15040674
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Health Co-Benefits: Embedding Health in the Climate Change Agenda

Abstract: A complex, whole-of-economy issue such as climate change demands an interdisciplinary, multi-sectoral response. However, evidence suggests that human health has remained elusive in its influence on the development of ambitious climate change mitigation policies for many national governments, despite a recognition that the combustion of fossil fuels results in pervasive short- and long-term health consequences. We use insights from literature on the political economy of health and climate change, the science–po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 91 publications
1
39
0
Order By: Relevance
“…The study results correspond with studies conducted in Canada and other developed countries which have revealed a silo approach to climate change governance and the isolation of public health from such structures as well as the lower prioritization of public health needs, and prominence of horizontal collaboration [ 26 , 27 , 123 ]. Other studies have also identified the influence of discourses and prominence of politics and vested interests on public health’s capacity [ 30 , 93 , 124 ]. Studies on stakeholder impacts have also linked stakeholder engagement to better evidence-informed policies, effective decision-making, successful uptake and acceptance of interventions, and better communication [ 36 , 58 , 60 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results correspond with studies conducted in Canada and other developed countries which have revealed a silo approach to climate change governance and the isolation of public health from such structures as well as the lower prioritization of public health needs, and prominence of horizontal collaboration [ 26 , 27 , 123 ]. Other studies have also identified the influence of discourses and prominence of politics and vested interests on public health’s capacity [ 30 , 93 , 124 ]. Studies on stakeholder impacts have also linked stakeholder engagement to better evidence-informed policies, effective decision-making, successful uptake and acceptance of interventions, and better communication [ 36 , 58 , 60 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, while governments engage in many climate change policy activities at various levels, these efforts are rarely coordinated with public health or embedded with public health needs [ 26 , 27 ]. Evidence also suggests that public health inclusion, framing, and engagement in the climate change discourse remains a challenge, accompanied by distinct context-specific barriers [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of inadequate, outdated or geographically differing concepts, methods, approaches or paradigms (Andersen, 2017;Balbus et al, 2014;Workman et al, 2018), as well as lack of knowledge, quantification and monetization (Creutzig & He, 2009;Mendez, 2015;Rashidi et al, 2017;Rennkamp & Boulle, 2018;Ščasný et al, 2015) are also referred to as reasons for non-uptake of co-benefits in policy.…”
Section: Policy Aspectsmentioning
confidence: 99%
“…As such, the environmental literature is increasingly considering the impact of environmental issues on human health as a means to (i) provide scientific evidence that environment and health should be considered jointly and (ii) increase recognition for environment in the wider policy agenda. This is particularly true for climate change where the focus on the health impacts of climate change has arguably helped embed the climate change agenda in the wider public health research (Costello et al, 2009;Workman et al, 2018). For example, comprising a multidisciplinary consortium of researchers the Lancet Commission on Climate Change and Health (Watts et al, 2015) aims to provide specific recommendations to government to enhance climate action, and monitor, assess and report on progress of health in the climate change agenda (Workman et al, 2018).…”
Section: Aligning Human Health and Ocean Plastic Pollution: A Co-benefimentioning
confidence: 99%
“…This is particularly true for climate change where the focus on the health impacts of climate change has arguably helped embed the climate change agenda in the wider public health research (Costello et al, 2009;Workman et al, 2018). For example, comprising a multidisciplinary consortium of researchers the Lancet Commission on Climate Change and Health (Watts et al, 2015) aims to provide specific recommendations to government to enhance climate action, and monitor, assess and report on progress of health in the climate change agenda (Workman et al, 2018). From a co-benefit perspective, framing or at least aligning environmental policy with public health have been used in China as a means to reduce emissions [Holdaway, 2013;Green and Stern, 2107], while in the USA, health co-benefits are publicly communicated as a key selling point in the climate change debate in an attempt to pursue climate action despite the politically toxic nature of the climate change debate (Jacob, 2016).…”
Section: Aligning Human Health and Ocean Plastic Pollution: A Co-benefimentioning
confidence: 99%